A Preliminary Study on the Impact of Passion and Financial Literacy on Pet Shop Business Performance - Rahman, Iradah; Sugangga, Rayyan; Santoso, Syahana Revi (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This qualitative case study explores the influence of financial literacy and entrepreneurial passion on the success of a micro pet shop business. Data were collected through an in-depth interview with the business owner to understand how internal factors shape financial behavior and business outcomes. The findings highlight that a strong emotional attachment to the business enhances the practical application of financial and digital competencies. Financial literacy is reflected in disciplined behaviors such as budgeting, saving, and making informed financial decisions, while digital literacy supports customer interaction and operational effectiveness. Together, these capabilities contribute to improvements in profit, capital growth, and market expansion. The study suggests that in niche sectors like pet retail, the integration of passion, financial knowledge, and digital skills is crucial for long-term sustainability. As an initial investigation, this research offers a foundation for broader studies involving more diverse MSME participants.